FIXED POINT THEOREMS FOR TWO PAIRED MAPPINGS IN FUZZY 2-METRIC SPACES - Pathak, Rohit (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
In this paper, we prove common fixed-point theorems for two pairs of self-mappings on fuzzy 2-metric space using weaker condition of the compatibility of the maps. Our results improve and the results of Sharma [10] in the sense that the completeness of the fuzzy 2-metric space and continuity of the mappings have been dropped. Our results also extend the results of Cho [2] to fuzzy 2-metric spaces. Mathematics Subject Classification. 47H10, 54H25.